Efficacy of Quinine Sulfate in Patients with Mild-To-Moderate COVID-19: A Randomized Controlled Trial - Irma Rahayu Latarissa; Melisa Intan Barliana; Anna Meiliana; Ida Paulina Sormin; Erizal Sugiono; Cissy Bana Kartasasmita; Irmansyah Irmansyah; Keri Lestari (The Prodia Education and Research Institute (PERI), 2023)
BACKGROUND: Before WHO revoked the emergency use authorization for Chloroquine (CQ) and Hydroxychloroquine (HCQ) because of their side effects, it was suggested to use these two drugs for COVID-19 therapy. In addition, another derivate of quinine, namely Quinine Sulfate (QS), showed good in silico and in vitro antiviral activity against SARS-CoV-2. Prior the WHO revocation, this study was conducted to evaluate the efficacy of QS in mild-to-moderate COVID-19 patients.METHODS: This was an adaptive, controlled, multicenter, randomized, double-blind clinical trial involving mild-to-moderate COVID-19 patients in Indonesia. The participants were divided into 2 groups: the control group (standard COVID-19 treatment + placebo) and the treatment group (standard COVID-19 treatment + QS). The primary outcome was the efficacy of QS based on clinical status using a 7-point ordinal scale. The secondary outcomes were the efficacy of QS in terms of the incidence and duration of oxygen supplementation, incidence of mechanical ventilation, and length of stay.RESULTS: No significant difference in the efficacy parameters studied was found between the control group and the treatment group. The difference in the mean oxygen saturation was also measured and the results showed a significant difference where the treatment group had higher mean oxygen saturation than the control group (p=0.001).CONCLUSION: Although not significant, the treatment group showed better therapy outcomes compared to the control group.KEYWORDS: clinical trials, efficacy, quinine, chloroquine, hydroxychloroquine